PENGARUH PERBEDAAN LAMA PERIODE PEMBERIAN PAKAN DAN LEVEL PROTEIN TERHADAP LAJU PAKAN, KONSUMSI PROTEIN, DAN KECERNAAN PROTEIN AYAM PELUNG UMUR 1 MINGGU SAMPAI 11 MINGGU - Sholeh, Tri; Sarengat, Warsono; Atmomarsono, Umiyati (Animal Agriculture Journal, 2012)
Productivity of Pelung chicken optimal must be supported by the provision of adequate food, both quality and quantity, to the feeding program should be carried out right on the pelung chicken as needed to serve as a guideline maintenance. The material used was 1 week old pelung chicken unsex as much as 96 tail that is placed on the 24 plots with a size of 60 x 60 x 70 cm, each row there are 4 chickens. Models of experimental design used was Randomized Complete Design (CRD) with 3 treatments ie T1 = treatment by administering Coarse Protein (PK) 18% for 3 weeks and PK 15% for 3 weeks; T2 = treated with PK 18% for 5 weeks and PK 15% for 5 weeks; and T3 = treatment with PK 18% for 7 weeks and then given PK 15% for 3 weeks and each of 8 replicates for each treatment. The parameters observed were feed intake, and feed rate. The data obtained were then analyzed using a variety of F test The results showed that the average of feed rate T1, T2 and T3 was 162.38 minutes 167.25 minutes and 156.83 minutes. The average consumption of protein T1, T2 and T3 32.23 grams, 31.38 grams and 33.02 grams. The average protein digestibility of 76.22% T1, T2 and T3 80.81% 78.93%. The analysis showed that the influence of different kinds of long periods of feeding and protein level and digestibility of feed protein, feed rate no significant effect (P> 0.05), while the fact protein intake is significantly effect (P> 0.05).Key words: pelung chicken, feeding, protein level, feed rate, protein intake, protein digestibility